LEGAL DIVERSIFICATION AS A STRATEGY TO REDUCE INVESTMENT RATIOS - Manuelia, Lidya; Uzliawati, Lia (JEA17: Jurnal Ekonomi Akuntansi, 2023)
Everyone who invests will want to get optimal profits with a growing capital value, whether using long-term investments or short-term investment products. Therefore, a strategy is needed in making investments. One of them is by investment diversification. Investment diversification is a widely accepted strategy for reducing investment risk. In analysing the portfolio, continuous analysis is needed in order to obtain relevant information, so that the target of portfolio formation through diversification provides optimal results. At the time when the traditional portfolio was recognised, the simple diversification of investments was the commonly used strategy, however, due to its inability to recognise the correlation between returns on different investments, simple diversification was replaced with efficient diversification. This study is aimed at conducting a comparative analysis between the simple and efficient diversification of investments, and to determine the combination of expected return and LQ-45 stock risk in order to select investments in Indonesia Stock Exchange through the establishment of an optimum portfolio.